Simulation and optimization of the thermal sterilization process of puree cans using the production of chestnut puree as an example - Wang, Wencheng; Wu, Jinqing; Zheng, Jiali; Wu, Zhiliang; Huang, Jinfeng; Lu, Yibin; Peng, Xiaoyan; Huang, Liqing (Frontiers in Microbiology, 2023)
In the production process of puree cans such as chestnuts cans , it is easy to browning due to excessive heating, which causes a lot of waste every year. The heat and mass transfer model of Chinese Chestnut Puree was established through the finite element method. The model simulated the change process of the temperature field, heat flow velocity field and F value during the production of Chinese Chestnut Puree. After comparing and confirming the effectiveness of the model through the thermal penetration test, the model was used to adjust and optimize the production process. For #9121 cans, the two-stage sterilization method was adopted. Through the sterilization method at 10-65-48-14/118-110 ℃, a sterilization effect equivalent to that of the original process at 10-86-24/121 ℃ was achieved, the browning problem of the product was alleviated, and the product quality was improved. This practice can also provide a reference for canning enterprises to adjust their production processes in the future.